2014
DOI: 10.1063/1.4869657
|View full text |Cite
|
Sign up to set email alerts
|

Coercivity and exchange bias of bismuth ferrite nanoparticles isolated by polymer coating

Abstract: Bismuth ferrite nanoparticles have been extensively investigated over the last few years due to their potential candidacy for application in future memory devices. However, all the work reported so far on bismuth ferrite nanoparticles is on agglomerated nanoparticles. Agglomerated particles can magnetically interact with each other. To utilize them for device application, it is useful to know the properties of the individual particles. Here, de-agglomeration of ∼75 nm bismuth ferrite nanoparticles is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
4
11
0
Order By: Relevance
“…2 also shows the magnication of partial 2q range from 31 to 33 degrees, which contains characteristic splitting of rhombohedral peak. The doublet near 32 remains same for all the samples and broadening is observed which can be attributed to decreasing values of lattice parameters due to incorporation of PANI 3 and it indicates that PANI might have formed the coordination with lattice oxygen, which has two major effects on BFO lattice (i) locally distort the crystal lattice of BFO by incorporation of PANI. Distortion of the local lattice is signicant factor for supporting the changes observed in optical properties.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…2 also shows the magnication of partial 2q range from 31 to 33 degrees, which contains characteristic splitting of rhombohedral peak. The doublet near 32 remains same for all the samples and broadening is observed which can be attributed to decreasing values of lattice parameters due to incorporation of PANI 3 and it indicates that PANI might have formed the coordination with lattice oxygen, which has two major effects on BFO lattice (i) locally distort the crystal lattice of BFO by incorporation of PANI. Distortion of the local lattice is signicant factor for supporting the changes observed in optical properties.…”
Section: Resultsmentioning
confidence: 84%
“…This brings Fe-Fe ions closer and contributes towards the changes in magnetic properties. 3 The successful polymerization of aniline onto the surface of BFO was conrmed by Fourier Transform Infrared Spectroscopy (FTIR), as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has led to extensive research primarily focused on physical property optimization, for example, magnetic property, in BFO by tailoring size of NPs. [9][10][11][12] The work on NPs of BFO has shown that they have size dependent ferromagnetism. The appearance of ferromagnetism in BFO, which in the bulk form is basically a G-type antiferromagnetic material with canted spins on a spiral chain with period of $62 nm has been explained as due to abrupt termination of spiral, canted spin chain, as well as structural disorder due to the strain at surface.…”
mentioning
confidence: 99%
“…17,18 BFO nanoparticles were synthesized using a soft chemical route combined with post synthesis annealing, reported earlier. 10,12 All the chemicals used are of analytical grade (99.9% purity). Synthesis involves a reaction of Bi(NO 3 ) 3 Á5H 2 O and Fe(NO 3 ) 3 Á9H 2 O in the presence of tartaric acid at 353 K, until the product is in sol-gel form.…”
mentioning
confidence: 99%